Pengaruh Jarak terhadap Persepsi Sehat Penghuni Perumahan Kecamatan Tebet Jakarta Selatan - Mohammad Aditya Ajie Wicaksono; Nur Intan Simangunsong; Benny Benyamin Suharto (Jurnal Lanskap Indonesia, 2021)
The poor environmental conditions in Jakarta indicate that housing residents are not healthy, therefor the need for green open spaces that are close to housing is very important. The purpose of this study is to determine the effect of green open space on the health perceptions of housing residents. The research method used is descriptive quantitative with primary data collection stages; limiting the distance of the research location area within a radius of 1-3 km; perform multiple linear regression analysis and cross-tabulation. The results of this study indicate that the negative coefficient is not unidirectional; the adolescent and elderly age group had a good healthy perception, reaches 42.7%; male gender showed a good healthy perception 35.4%; Housing residents who do not work have a healthy perception of 33.3%. The perception of health decreases with increasing distance and is increasingly visible in residents who live within 1-3 km of green open space. This research serves as input to related agencies that the minimum distance of green open space to housing is 300-1000 m because it is important to provide good health effects for housing residents.